2005
DOI: 10.1177/0887302x0502300102
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationships of Grading, Sizing, and Anthropometric Data

Abstract: Grading is the process used to accomplish the sizing of manufactured clothing. Th e focus of our research was to question the belief that the foundation for grading is size measurements that are based on anthropometric data. Our review of literature established that grading preceded size charts. Forty size charts for women's clothing were examined for correspondence with anthropometric research. Four structural assumptions that did not match anthropometric research were identifi ed. Criteria were developed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 4 publications
1
32
2
Order By: Relevance
“…Users can base their decision on their previous experience. But each company has its own sizing, and what is more, this can change over time (Schofield and LaBat, 2005). This is therefore not a reliable strategy (Sindicich and Black, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Users can base their decision on their previous experience. But each company has its own sizing, and what is more, this can change over time (Schofield and LaBat, 2005). This is therefore not a reliable strategy (Sindicich and Black, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To produce garments that fit the population, it follows that the sizes must correspond to real grouping. However, this is often not the case, as indicated by the results obtained by Shofield and LaBat [1]. Their study of forty size charts for women's clothing showed that the different sizes are defined using arbitrary constant intervals between sizes, all vertical measurements increase as the size increases and that the differences between the principal girths are constant for all sizes.…”
Section: Introductionmentioning
confidence: 81%
“…Grading begins with a garment pattern that has been created for a fit model or dress form in a designer or manufacturer's base size. Grading is accomplished by applying increases (for larger sizes) or decreases (for smaller sizes) at key locations of each pattern piece to create a pattern in the next size (Schofield & LaBat, 2005). The differences (grade) between retailers' sizes were recorded from the 47 retailers' online measurements in Appendix 2.…”
Section: Sizing and Comfortmentioning
confidence: 99%